Folding-induced in-plane birefringence in homeotropically aligned graphene-oxide liquid crystal films formed by solution shear. Issue 3 (19th February 2022) - Trung, Le Gia; Subedi, Subhangi; Rella, Avinash Kumar; Kumar, Vineet; Kang, Shin-Woong
ABSTRACT: Graphene-oxide (GO) has been widely explored as a functional two-dimensional (2D) material. The GO-flakes self-assemble into colossal sheets of 2D aggregates with extreme flexibility and the GO-dispersion in water forms an alternately layered phase with nematic order. Highly ordered supramolecular anisotropic GO films can be fabricated by a hydraulic shear. For a uniform in-plane shear, it is generally known that GO aligns tangential to the shear plane, resulting in homeotropic orientation of the optic axis with no in-plane birefringence. However, it surprisingly results in uniform in-plane birefringence with the optic axis (Δ n < 0) aligned perpendicular to the shear direction. The in-plane birefringence originates from the folding deformation of homeotropically aligned GO layers, rather than reorientation of pristine GO flakes. 2D GO aggregates are very large and flexible so that prone to be deformed by external force, rather than reorientation. For the alternately layered GO-LC phase, drying is a directional process so that major compression occurs predominantly along the layer-normal. As a result, both folding width and film thickness are reduced considerably and the folded band protrudes during a drying process. This folding-induced in-plane birefringence of GO-LCs provides useful insights for processing anisotropic 2D materials, beneficial for various electrical, optical, and mechanical applications. Graphical Abstract: uf0001